Investigation on Modulus of Elasticity of Badminton String by Response Surface Methodology - Feng Ji (Advances in Materials Science and Engineering)
Modulus of elasticity (MOE) is one of the important indexes to evaluate the performance of badminton string. In this work, a series of tensile testing were performed to explore the changes in MOE at different temperature, humidity, and tensile rate. Based on the experimental results, an MOE model for badminton string was developed by using response surface methodology. Meanwhile, the significant contribution of each variable and two-factor interactions on MOE were investigated by analysis of variance. The special aim of this work was to determine the optimal processing parameters for maximum MOE for the higher performance of badminton string, and those processing parameters are temperature of 10.7°C, humidity of 0.19%, and tensile rate of 59.98 mm/min, which were propped to be adopted for the actual use of badminton string.